Late Pleistocene temperature history of Southeast Africa: A TEX86 temperature recordfrom Lake Malawi - Woltering, Martijn; Johnson, Thomas; Werne, Josef; Schouten, S.; Damste, J. (Elsevier Science BV, 2011)
Wepresent a TEX86-derived surfacewater temperature record for LakeMalawi that provides the first continuous continental record of temperature variability in the continental tropics spanning the past ~74 kyr with millennial-scale resolution. Average temperature duringMarine Isotope Stage (MIS) 5A was 26.5 °C, with a range from25.7 to 27.3 °C, comparable toHolocene temperatures. MIS 4was a relatively cold period with temperatures generally decreasing from25.5 °C at 68 ka to a minimumof 20 °C at ~60 ka, 1.5–2 °C colder than the Last Glacial Maximum (LGM). Termination of MIS 4 is characterized by a rapid increase of 3–4 °C in only ~0.5 kyr. Temperatures were relatively stable throughout MIS 3 at the resolution of this study, with an average of 23.8 °C and a range from 25.1 to 22.9 °C. The lack of millennial-scale temperature variability during MIS 3 suggests that Lake Malawi's documented response to the bipolar seesaw (Brown et al., 2007) is not reflected in its thermal history. Our temperature estimates for the LGM and Holocene are consistent with a previously published TEX86 record from Lake Malawi with a temperature of ~22.6 °C for the LGM, ~25–26 °C in the mid Holocene and~25–28 for the lateHolocene. In general the present extended TEX86 record indicates that temperature variability in tropical East Africa during late MIS 5 and MIS 4 was as great as that associated with the deglaciation and Holocene. A decrease in Southern Hemisphere insolation between 70 and 60 ka may have played an important role in forcing temperaturesduringMIS 4, but after 60 ka other factors, suchas the extent of the polar ice sheets, or atmospheric CO2 may have forced temperature in tropical Africa to a greater extent than local summer insolation.